Lewis Acidic Ionic Liquids As New Addition Catalyst For Oleic Acid To Monoestolide Synthesis - Adnan, Nadia Farhana; Mohamad Nordin, Nor Asikin; Hamzah, Noraini; Yarmo, Mohd Ambar (Journal of Science and Technology, 2010)
Estolide compound has a large potential in many industrial applications such as biodegradable lubricants and in cosmetic formulation. In this study, monoestolide can be prepared by addition reaction of oleic acid under vacuum-reflux and solvent free condition for 10 hours at 85 °C in the presence of solid zinc chloride anhydrous (ZnCl2), choline chloride (ChCl) and ionic liquids (IL) ChCl-ZnCl2, ChCl-FeCl3, ChCl-SnCl2, ChCl-CuCl2 as homogenous acid catalysts. These reactions were compared with common homogenous catalyst namely sulfuric acid (H2SO4). The FTIR analysis show that addition reaction using the above catalysts showed the presence of three new peaks at 1732 cm-1 for C=O ester, 967.0 cm-1 for trans-CH=CH and 1176 cm-1 for C-O-C which confirmed the existence of monoestolide. The LC-MS results showed peak for the present of new monoestolides at retention time (tR) 12.3 min corresponding to m/z 563.48. Among the IL, ChCl-ZnCl2 surprisingly exhibited higher activity which is 98 % acid oleic conversion and 80 % selective for the synthesis of monoestolides. As a result, this IL gave two potential functions as a solvent as well as a green catalyst for monoestolide synthesis from oleic acid.